THE INFLUENCE OF FAMILY EDUCATION ON THE PERSONALITY DEVELOPMENT OF A MENTALLY RETARDED CHILD - Kuz'mina I. A., Dormidontov R. A. (Psychological and Pedagogical Support of General, Special and Inclusive Education of Children and Adults, 2024)
This article highlights the topic of the influence of family and family education on the formation of the personality of a child with mental retardation. The connection between the personality development of children of this group and various approaches to family education is investigated
Keywords: воспитание; личность; personality; influence; upbringing; child with mental retardation; стиль воспитания; parenting style; ребенок с умственной отсталостью